Pengaruh Layanan Bimbingan Klasikal Dengan Metode Jigsaw Terhadap Pemahaman Kesehatan Reproduksi Siswa Kelas IX SMP Negeri 2 Limbangan - Any Anjany; Heri Saptadi Ismanto; Agus Setiawan (LPPM Politeknik Pratama, 2023)
The purpose of this study is to determine whether there is an influence of classical guidance services using the Jigsaw method on students' understanding of reproductive health. This type of research is quantitative research in the form of a True Experiment Design with a Pretest-Posttest Control Design. The population in this study were class IX students. Based on the pretest results of the reproductive health scale in class IX students, it shows that in the class interval 104-128 as many as 2 students or 6% are in the very high category, posttest results of the reproductive health scale in class IX students showed that in the 104-128 interval class as many as 6 students or 17% were in the very high category, then the hypothesis that classical guidance services with the Jigsaw method have an effect on increasing students' understanding of reproductive health has a significant difference, seen from the results of pretest and posttest calculations.